Ship weather routing: A taxonomy and survey - Zis, Thalis; Psaraftis, Harilaos N.; Ding, Li (My University, 2020)
Ship weather routing has seen considerably increasing attention in recent years in both academia and industry. Problems in this area consider finding the optimal path and sailing speed for a given voyage considering the environmental conditions of wind and waves. The objectives typically consider minimizing operating costs, fuel consumption, or risk of passage. This paper presents a survey of weather routing and voyage optimization research in maritime transportation, explaining the main methodological approaches, and the key disciplines that are dealing with this problem. The main methodologies used to solve the weather routing problem include the isochrone method, dynamic programming, calculus of variations, the use of pathfinding algorithms and heuristics, while in recent years artificial intelligence and machine learning applications have also risen. Most of these methodologies are well established, and have not changed significantly throughout the years, although applications with a combination of these methods have been used. A taxonomy is subsequently presented based on the discipline, application area, methodological approach, and other important parameters. Considering the steep increase in the number of research papers published in recent years, this paper also seeks to propose future research topics in the field. The paper highlights the need to standardize the reporting of savings through weather routing, to facilitate comparisons between methodologies, which could be achieved through the creation of benchmarking instances.
Keywords: Voyage optimization; Maritime transport; Ship weather routing; Speed optimization